Kontribusi Tripartit Dalam Mempersiapkan Transisi Mulus Anak PAUD ke SD - Astriya, Baiq Roni Indira (AWLADY : Jurnal Pendidikan Anak, 2025)
The transition from early childhood education (PAUD) to primary school is a critical milestone in a child's developmental journey. This study investigates the key factors influencing a smooth transition, specifically examining the roles of parents, teachers, and the surrounding environment, with an emphasis on socio-emotional readiness and academic preparedness. Through a comprehensive literature review, findings indicate that holistic support from caregivers, structured transition programs, and targeted interventions are essential for a positive school experience. Early socio-emotional development in PAUD, which fosters resilience and adaptability, plays a significant role in equipping children for the structured setting of primary school, aligning with Vygotsky's theory on the importance of social interaction in cognitive growth. Academic readiness, particularly in foundational literacy and numeracy, builds children's confidence and preparedness for structured learning. Additionally, active parental engagement and consistent daily routines facilitate the transition by enhancing children's curiosity and comfort within the school environment. Recommendations include implementing child-centered transition activities to reduce stress and promote a positive school experience. This study underscores the importance of collaboration between educators and families to support a seamless transition. Future research should focus on longitudinal studies to measure the long-term impact of early transition interventions on academic and social outcomes in primary education.